2020
DOI: 10.1073/pnas.2001520117
|View full text |Cite
|
Sign up to set email alerts
|

The pseudo-caspase FLIP(L) regulates cell fate following p53 activation

Abstract: p53 is the most frequently mutated, well-studied tumor-suppressor gene, yet the molecular basis of the switch from p53-induced cell-cycle arrest to apoptosis remains poorly understood. Using a combination of transcriptomics and functional genomics, we unexpectedly identified a nodal role for the caspase-8 paralog and only human pseudo-caspase, FLIP(L), in regulating this switch. Moreover, we identify FLIP(L) as a direct p53 transcriptional target gene that is rapidly up-regulated in response to Nutlin-3A, an M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 52 publications
4
34
0
Order By: Relevance
“…However, recent data suggest that the overall net charge of the p53 C-terminus may play an important role in repressing its activity, with an un-acetylated ‘acidic’ C-terminus being read by SET, much like a histone, inhibiting its acetylation ( 118 ). Modulating the activities of regulators of p53 PTMs, such as inhibitors of HDACs and other co-factors, have shown potential to promote p53 induced cell death alone or in combination with DNA-damaging agents ( 130–133 ), but the underlying mechanisms remain poorly understood.…”
Section: Chromatin-engaged Cofactors Of P53mentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent data suggest that the overall net charge of the p53 C-terminus may play an important role in repressing its activity, with an un-acetylated ‘acidic’ C-terminus being read by SET, much like a histone, inhibiting its acetylation ( 118 ). Modulating the activities of regulators of p53 PTMs, such as inhibitors of HDACs and other co-factors, have shown potential to promote p53 induced cell death alone or in combination with DNA-damaging agents ( 130–133 ), but the underlying mechanisms remain poorly understood.…”
Section: Chromatin-engaged Cofactors Of P53mentioning
confidence: 99%
“…These differential effects of p53 activation are likely a combination of tissue specific accessibility of p53 target and differential ‘priming’ of cell types for cell death ( 212 ), as has recently been shown with HDAC inhibitors that synergistically induce p53-dependent cell death in combination with Nutlin-3a or chemotherapy. This is mediated through HDAC inhibitors blocking activation of a subset of p53 targets including the pro-survival caspase-8 inhibitor FLIP, which releases the brake on ‘priming’ of pro-apoptotic targets TRAILR2, BAX, and PUMA ( 130 ). Similarly, treatment of MCF7 cells with the DNA methylation inhibitor decitabine led to de novo chromatin accessibility and p53 binding, suggesting that changes in cell state and pharmaceutical treatments can alter the binding and activity of p53 ( 52 ).…”
Section: Dissecting Ubiquitous and Cell Type-specific Direct P53 Targmentioning
confidence: 99%
“…Mechanistically, the effects of FOLFOX on FLIP expression were not due to suppression of transcription; indeed, mRNA expression of FLIP(S) was upregulated at 24h by ~2-fold and FLIP(L) was upregulated by ~5-fold at 48h ( Figure 6A ). Inhibition of histone deacetylases (HDACs) has previously been reported by us and others to result in reduced expression of both splice forms of FLIP, at transcriptional and post-translational levels and augment cell death induced by activators of extrinsic cell death [30-32]. It was therefore notable that FOLFOX treatment downregulated expression of the Class-I HDACs (HDAC-1, −2 and −3) as did tolinapant/TNFα ( Figure 6B ).…”
Section: Resultsmentioning
confidence: 59%
“…Compared to a HCT116 caspase-8 CRISPR knockout model in which cell death induced by the tolinapant/TNFα-FOLFOX combination was almost completely abrogated ( Figure 5C/D ), significant cell death was still observed in response to the combination in the FLIP(S) overexpressing model ( Figure 5B ), suggesting that additional factors other than FLIP downregulation contribute to the effects of the combination. The role of caspase-8’s other paralog caspase-10/CASP10 as a regulator of apoptotic cell death is controversial, with both pro- and anti-apoptotic roles described [28-30]. We found that co-treatment of HCT116 cells with tolinapant/TNFα/FOLFOX dramatically reduced the levels of procaspase-10 expression ( Figure 5C ).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation